The practice of development the category essence of notions in the context of piano school: history and theory analyse (Pedagogy of Higher and Secondary Education, 2006)
In this article are ordered ideas from history of development theoretic notions in the context of piano school. propose author's comprehension category “piano school” and modem view on problem of its take with pedagogical technologies of take possession of forteptano.
Keywords: piano school; category essence